2002
DOI: 10.1016/s0736-0266(02)00007-4
|View full text |Cite
|
Sign up to set email alerts
|

Lead alters parathyroid hormone‐related peptide and transforming growth factor‐β1 effects and AP‐1 and NF‐κKB signaling in chondrocytes

Abstract: The skeletal system is an important target for lead toxicity. One of the impacts of lead in the skeleton, the inhibition of axial bone development, is likely due to its effect on the normal progression of chondrocyte maturation that is central to the process of endochondral ossification, Since little is known about the effect of lead on chondrocyte function/maturation, its impact on ( I ) growth factor-induced proliferation, (2) expression of maturation-specific markers type X collagen and BMP-6, and (3) the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 48 publications
4
26
0
2
Order By: Relevance
“…Since BMP signaling is essential for chondrocyte maturation, it is possible that the effect is secondary to downregulation of this signaling pathway, as was observed in vitro. Thus, although Pb stimulates chondrogenesis, it reduces chondrocyte maturation and thereby results in delayed endochondral bone formation, as has been previously documented (112). Consistent with these in vitro and in vivo data, Pb exposure has been found to inhibit fracture healing in mice, with complex effects noted on chondrogenesis and chondrocyte maturation (113).…”
Section: The Influence Of Pathologic Stress On Chondrogenesis and Endsupporting
confidence: 69%
“…Since BMP signaling is essential for chondrocyte maturation, it is possible that the effect is secondary to downregulation of this signaling pathway, as was observed in vitro. Thus, although Pb stimulates chondrogenesis, it reduces chondrocyte maturation and thereby results in delayed endochondral bone formation, as has been previously documented (112). Consistent with these in vitro and in vivo data, Pb exposure has been found to inhibit fracture healing in mice, with complex effects noted on chondrogenesis and chondrocyte maturation (113).…”
Section: The Influence Of Pathologic Stress On Chondrogenesis and Endsupporting
confidence: 69%
“…This study demonstrates that environmental exposure to osteotoxic substances results in contamination levels measurably present in bone graft regardless of the source. Animal studies have suggested that comparable degrees of lead exposure have toxic effects on skeletal tissue and fracture healing [3,4,6,15,16,18,[20][21][22][23]. In addition, clinical studies are present in the literature demonstrating deleterious effects on bone healing, bone remodeling, and skeletal development [5,12,14].…”
Section: Discussionmentioning
confidence: 99%
“…2,3,46,51 Similarly, alterations in PTHrP signaling can have effects on transforming growth factor-beta and can lead to functional changes in activator protein-1, nuclear factor-B, E26 transformation-specific sequence-1, and specificity protein-1 signaling. 32,34 PTHrP also can inhibit the apoptotic effects of functional mutations in fibroblast growth factor, resulting in decreases in Bcl-2 expression and apoptosis. 52 Finally, PTHrP can be a potent tumor angiogenic factor.…”
Section: Discussionmentioning
confidence: 99%